2021
DOI: 10.1515/jbcpp-2020-0490
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin promotes behavioral recovery and biomolecular changes of melanocortin-4 receptor in mice with ischemic stroke

Abstract: Objectives Ischemic stroke is known as a common causes of disability, lower psychological well-being as well as preventable death. The pathogenesis of ischemic stroke process becomes worse immediately after oxidative stress occurs. One of the flavonoids with antioxidant abilities is quercetin. This study was aimed to investigate quercetin administration on the behavioral functions (motor and sensory) and expression of melanocortin-4 receptor (MC4R) in mice with ischemic stroke. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The pathogenesis of ischemic stroke mainly includes oxidative stress, inflammation, apoptosis and so on. One of the flavonoids with antioxidant capacity is quercetin, which can promote the behavioral recovery and biomolecular changes of melanocortin 4 receptors in ischemic stroke mice [11] . The pharmacological effects of saffron are attributed to the presence of crocin and saffron aldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…The pathogenesis of ischemic stroke mainly includes oxidative stress, inflammation, apoptosis and so on. One of the flavonoids with antioxidant capacity is quercetin, which can promote the behavioral recovery and biomolecular changes of melanocortin 4 receptors in ischemic stroke mice [11] . The pharmacological effects of saffron are attributed to the presence of crocin and saffron aldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…Ye et al (2021) showed that quercetin reduced neuropathic pain in chronic constriction injury (CCI) rats by mediating the AMPK/MAPK pathway. Ulya et al (2021) found that quercetin promotes behavioral recovery in mice with IS, which may be related to the regulation of the melanocortin-4 receptor (MC4R). Zhou et al (2020) found that kaempferol could reduce the inflammatory injury of PC12 cells induced by oxygen and glucose deprivation (OGD) and reoxygenation (OGD-reoxygenation) by regulating the SIRT1/P66shc signaling pathway, indicating that kaempferol may be an effective intervention option for IS.…”
Section: Discussionmentioning
confidence: 99%
“…Five mice per group were counted based on the previous study in producing mouse stroke models and by using the calculation for value “E”. 12, 21 The sample size was increased to eight mice per group to anticipate the number of animals suffering from death after stroke induction. 22 Forty mice were divided into five groups: sham group (mice were operated without arterial blockade), stroke group, and stroke groups treated with quercetin at 50 mg/kg, 100 mg/kg, and 200 mg/kg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, increasing MC4R mRNA expression has been associated with improved neuronal recovery. 11, 12 Stroke causes oxidative stress, which leads to apoptosis. The nuclear factor 2 (Nrf2)-associated erythroid 2 pathway plays a critical role in decreasing the effects of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%